CEO power and tax avoidance: An empirical study of manufacturing companies in Indonesia - Zunianto, Anugrah Pamungkas Wijil; Narsa, Niluh Putu Dian Rosalina Handayani; Lukita, Carolyn (Universitas Hayam Wuruk Perbanas, 2024)
This study aims to empirically examines the relationship between CEO power and tax avoidance. The lack of consistent empirical evidence regarding the relationship between CEO power and tax avoidance strategies encourages a deeper investigation into the mechanisms underlying this relationship. This study examines various aspects of CEO power and their impact on tax avoidance, thereby providing a more detailed under-standing of these complex interactions. The sample used in this study is 301 manufac-turing companies listed on the Indonesia Stock Exchange (IDX) for the period of 2015-2019. The data obtained are analyzed using SPSS version 20 software with multiple linear regression analysis. The results of this study show that expert power and prestige power have a positive relationship with tax avoidance, while ownership power has a negative relationship with tax avoidance. It is expected that this study provide theoretical benefits as a reference and knowledge for further research and practical benefits that are useful for the Directorate General of Taxes to formulate policies to reduce the risk of tax avoidance.